Framework for Inter Faith Dialogue in Al Sharia Al Islamiyah (Part I) - Dr. Muhammad Zia ul Haq (The Islamic Culture, 2018)
Islam being a unique and youngest in world religions has related itself to the most of the pre-Islamic religions. Islam's recognition of other religions as legitimate religions is essence of Islamic beliefs, which is reflected in the rulings of al-Sharia al-Islamiya . Its relations with other religions are indicating the world view of Islam. al-Sharia's view of God, the reality of man and his place in the universal, importance of religious diversity, legislation regarding non-Muslims are providing sufficient theological and legal grounds on which Muslims are regulating their relations with the followers of other religions. Islam's relations with Judaism, Christianity and Sabaeanism were crystallized first by God through direct revelation in al-Qur'an.